Coffee tokens and trade tokens: historical inheritance - Vargas Zamora, José A (2020)
Received: 10-18-2019 Approved: 11-29-2019 ABSTRACT  In Costa Rica during the mid XIX century there was a significant increase in the number of new coffee plantations. The need to pay the workers, together with the scarcity of low denomination silver coinage, forced the introduction of a temporay private form of payment, coffee tokens, that were given to the workers for each unit of coffee harvested and were exchanged for money usually at the end of the week. At the end of the XIX century the opening of the railroad tracks to the Caribbean coast and the development of banana plantations along its sides promoted the introduction of another form of private temporary payment, trade tokens, which were exchangeable for groceries or utensils at commercial posts along the tracks. In this work we analize the differences and uses of these two forms of payment, include examples of both, and make suggestions for the study and preservation of this historical inheritance.